Economic opportunities for the implementation of the rotel concept in the practice of the regional tourism industry - Temyakova, Tatiana Vitalievna; Cherevichko, Tatiana Viktorovna (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. The introduction provides a justifi cation for the use of rotels as hotels on wheels in the practice of tourism business. It is noted that traveling to remote destinations using motor vehicles can be comfortable, which is achieved through the implementation of the rotel concept. Theoretical analysis. The concept of “rotel” is absent in the norms of Russian law, which makes it diffi cult to defi ne the analyzed term unambiguously. Rotel can be applied both to cruise trains and rolling stock of land road transport. Despite the growing popularity of tourist trains, one should not underestimate the relevance of rotels moving along highways. Empirical analysis. An analysis of the economic possibilities of introducing the rotel concept into the practice of the Saratov region tourism industry has shown the limited fi nancial resources of Saratov tour operators for the implementation of the project. The market leaders demonstrate positive dynamics of net profi t, which can be used for the development of hotels on wheels, however, the most suitable facilities for the implementation of the rotel concept are the transport companies of the Saratov region. The paper analyzes the bus tours of a tour operator, one of the tourism industry leaders and draws conclusions about the likely demand for routes using rotels. An indirect evidence of this type of transport popularity is the growing demand for Saratov tourists to travel around Russia. The fi rst stage to the implementation of this concept may be options for tour routes in the home region. Results. The implementation of the rotel concept is an attractive direction for the development of the tourism industry from the point of view of the market. Such an idea can surprise tourists and get an emotional response from them. A promising option would be the cooperation of transport companies, in the future – owners of rotels, and tour operators chartering rotels in order to implement the formed tourist products.